Income, Demographics, and Life Experiences of Clinical-Forensic Psychologists in the United States - Neal, Tess M.S.; Line, Emily N. (Frontiers in Psychology, 2022)
We provide aggregate data about income, demographics, and life experiences of women and men practicing clinical-forensic psychology primarily in the United States (N = 376). We examine how these variables relate to one another, as well as how gender demographics of the field have changed over time. The average hourly rate charged by psychologists for forensic work, aggregated across all types of referral questions, regions, and employment settings is $280.23 (US Dollars; SD = $108.12; median and mode = $250). Total median annual income is $125,000 - $149,999 and mode is $100,000 - $124,999. Men’s annual income (median = $175,000 - $199,000) is significantly higher than women’s (median = $100,000 - $124,999) even while controlling for years of experience and number of hours worked per week. Women forensic psychologists earn $0.83 for every $1.00 men make. Having a PhD is disproportionately associated with men and PsyD with women; however, the difference is not significant once controlling for years of experience. Employment type related to pay, such that people in private practice make significantly more than those who work in institutions (e.g., prisons, hospitals) or universities. Year of highest degree associated with employment type, such that people in practice longer are more likely to be in private practice. Although we expected caretaking responsibilities and children would relate to gender and pay, no differences emerged in this sample. Women are more likely than men to have completed a formal postdoctoral fellowship in forensic psychology, even when controlling for year of highest degree. Regarding the gender composition of the field over time, we calculated the Index of Dissimilarity for each five year increment spanning 1965-2019. Before the late 1990s, proportionally more men entered the field; after the late 1990s, proportionally more women entered. We discuss the promising and less promising implications of these findings for gender equity and work-life management in forensic psychology, as well as how professionals in the field and students might make use of these data.